2021
DOI: 10.1186/s13005-021-00260-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between problematic social media use and memory performance in a sample of Lebanese adults: the mediating effect of anxiety, depression, stress and insomnia

Abstract: Background Psychological factors such as depression, anxiety, stress and insomnia and problematic social media use are able to alter our memories and might have an impact on memory function and retrieval. More studies are needed to better understand the relationship between memory performance and mental health disorders, especially the ones that could be related to problematic social media use. The objective of this study was to evaluate any association between problematic social media use, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…However, this research did not find a gender effect on Internet or smartphone use disorder and working memory capacity. The mediating effect of depression, anxiety, and stress between problematic social media use and memory capacity was researched [45]. In this research, the Memory Awareness Rating Scale (MARS-MPS) was used to evaluate memory performance.…”
Section: Internet or Smartphone Use Disorder And Working Memory Capacitymentioning
confidence: 99%
“…However, this research did not find a gender effect on Internet or smartphone use disorder and working memory capacity. The mediating effect of depression, anxiety, and stress between problematic social media use and memory capacity was researched [45]. In this research, the Memory Awareness Rating Scale (MARS-MPS) was used to evaluate memory performance.…”
Section: Internet or Smartphone Use Disorder And Working Memory Capacitymentioning
confidence: 99%
“…A Lebanese study done by Obeid et al 45 had showed that high PIU was found in 3.6% of Lebanese adolescents while 40% had occasional and frequent internet users. 45 Previous studies conducted among Lebanese adults have evaluated the association between problematic social media use and loneliness, 46 alexithymia, 47 memory performance, 48 alcohol use disorder 49 and mental health issues (depression and anxiety). 50 No studies have studied the association between PIU and mental health issues among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Problematic social media is also significantly associated with higher anxiety among the Lebanese population. 20 Another, less prevalent, 9 approach, but the one chosen in the present research, denotes anxiety as a cause of SMF. The cogent rationale behind this type of directionality rests on some theoretical perspectives.…”
Section: Define Smf Asmentioning
confidence: 99%
“… 17–19 Problematic social media is also significantly associated with higher anxiety among the Lebanese population. 20 …”
Section: Introductionmentioning
confidence: 99%